ANALISIS TERHADAP EFEKTIVITAS KEBIJAKAN PEMBERIAN ASIMILASI BAGI NARAPIDANA LAPAS KELAS I MEDAN DI MASA PANDEMI SEBAGAI BENTUK ANTISIPASI PENYEBARAN COVID - umi Khairiah; Apri Amalia (Jurnal Ilmiah Advokasi, 2022)
The Covid-19 pandemic has become a national disaster that has become a frightening specter for inmates, because the opportunities for transmission are very large due to the overloaded conditions of prisons, besides that the Covid-19 assimilation policy has caused public concern about increasing crime during the Covid-19 pandemic carried out. assimilation prisoners. The purpose of this study was to determine whether the assimilation program for prisoners during the Covid-19 pandemic could be effective in preventing the transmission of Covid-19 and the impact of providing assimilation for prisoners in terms of increasing crime in the city of Medan. The research method used is normative juridical and empirical juridical. The results of this study on the assimilation of COVID-19 are an attempt by the government to break the Covid-19 chain in prisons. created because of the prison's overcapacity. This policy has been reviewed and is considered effective in achieving the target to reduce the spread of Covid-19. The impact of releasing assimilated prisoners is a boon to prisoners and does not have the effect of increasing crime. Crimes committed by prisoners of assimilation are only 1%.Keywords: Anticipation; Effectiveness; Policy; Covid-19 Assimilation; Spread of Covid-19.